2017
DOI: 10.1016/j.physe.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Semimetal behavior of bilayer stanene

Abstract: Stanene is a two-dimensional (2D) buckled honeycomb structure which has been studied recently owing to its promising electronic properties for potential electronic and spintronic applications in nanodevices. In this article we present a first-principles study of electronic properties of fluorinated bilayer stanene. The effect of tensile strain, intrinsic spin-orbit and van der Waals interactions are considered within the framework of density functional theory. The electronic band structure shows a very small o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In addition, Khan et al has recently reported a finite band gap in the stanene/h-BN heterobilayers [37]. On the other hand, as reported by Evazadde et al [38], the electronic band structure of the bilayer stanene shows a non zero band gap with reasonably high electron conductivity. In this context, the intriguing prospect of stanene and silicene heterostructures as well as bilayer stanene in thermoelectric applications urges further investigation and modeling of the thermal transport in stanene and silicene based nanostructures with a view to lowering the thermal conductivity in these structures.…”
Section: Introductionmentioning
confidence: 76%
“…In addition, Khan et al has recently reported a finite band gap in the stanene/h-BN heterobilayers [37]. On the other hand, as reported by Evazadde et al [38], the electronic band structure of the bilayer stanene shows a non zero band gap with reasonably high electron conductivity. In this context, the intriguing prospect of stanene and silicene heterostructures as well as bilayer stanene in thermoelectric applications urges further investigation and modeling of the thermal transport in stanene and silicene based nanostructures with a view to lowering the thermal conductivity in these structures.…”
Section: Introductionmentioning
confidence: 76%
“…Stanene exhibits several remarkable features, including large spin–orbit gaps, topological superconductivity, quantum anomalous Hall behavior, giant magnetoresistance, and efficient thermoelectricity [ 73 ]. Additionally, there have been numerous studies showing that measures such as doping with metal atoms can have a large effect on the structural and electrochemical properties of Stanene [ 74 , 75 ].…”
Section: Research Progress Of 2d Electrode Materials For Edlcsmentioning
confidence: 99%
“…They found that the band structure indicates a minor overlap between valence band maxima and conduction band minima at the Dirac, this indicates properties of semimetal in the two-layer SnF system. Their results suggest that the bilayer SnF is not a potential material for topological insulators [11]. Abbasi & Sardroodi carried out calculations on the band-gap variations in stanene via density functional theory, and the effects of elemental doping were taken into account.…”
Section: Introductionmentioning
confidence: 99%